Transience analysis of bursty traffic with erbium doped fiber amplifiers - Reis, C. (2010)
Copyright © [2009] IEEE. Reprinted from ICTON 2009. ISBN 978-1-4244-4826-5. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.